KERUKUNAN ANTARAGAMA PERSPEKTIF FILSAFAT PERENNIAL REKONSTRUKSI PEMIKIRAN FRITHJOF SCHUON - NGAINUN NAIM (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
This article discusses the role of perennial philosophy in developing interligious harmony. One of prominent figures on perennial philosophy is Frithjof Schuon. Perennial philosophy has a constructive view in understanding religions. In the perennial philosophy perspective, the religious diversity is a reality that cannot be avoided. Schuon views that religion consists of exoteric and esoteric dimensions. Exoteric dimension is a particular dimension existed in every religion which is different between one and another. An exoteric statement that regards it itself as the only truth owner is also contradict with axiomatic truth that there is no unique fact in reality. Meanwhile, esoteric dimension is universal dimension that become common platform of all religions. The consciousness to esoteric dimension play significant role in building the harmony. This consciousness becomes the faundation for developing diversity consciousness. The consciousness of this religious diversity becomes the key word in developing interreligious harmony of life. Keywords: perennial philosophy, harmony, Frithjof Schuon